Prevalence of hypotension in populations of the Russian Federation and the United States of America according to 30-year follow-up - V. G. Vilkov; S. A. Shalnova; Yu. A. Balanova; S. E. Evstifeeva; A. E. Imaeva; A. V. Kapustina; G. A. Muromtseva (Кардиоваскулярная терапия и профилактика, 2020)
Aim. To study the prevalence of hypotension according to several criteria in the Russia and the USA.Material and methods. We used data of Russian population studies performed in 1975-1982 and ESSE-RF study performed in 2012-2014 at the National Medical Research Center for Therapy and Preventive Medicine. A comparison was made with the data of cross-sectional stu - dies of the US population — National Health and Nutrition Examination Survey (NHANES): NHANES II (1976-1980) and Continuous NHANES (2007-2012). We analyzed age, sex, and systolic and diastolic blood pressure. The prevalence of individuals with hypotension was calculated in men and women of five age groups using four different criteria for hypertension.Results. The prevalence of hypotension in studies of different years according to different criteria was as follows: in the Russia — 0,3-9,0% in men and 2-15% in women; in the USA — 5-30% in men and 8-45% in women. In age group >30 years, the prevalence of hypotension in Russia, by most criteria, decreased approximately by 50% in men and did not change in women. In the United States, according to all criteria, the prevalence in men and women has increased 2-3 times.Conclusion. The prevalence of hypotension in the adult population ranges from decimal percentages to 45% and varies many times depending on the selected criterion.